A Path to the Stars: The Evolution of the Species - Fabrizio Vitali; Guido Chincarini; Mario Zannoni; Stefano Covino; Emilio Molinari; Stefano Benetti; Carlotta Bonoli; Favio Bortoletto; Enrico Cascone; Rosario Cosentino; Francesco D'Alessio; Paolo D'Avanzo; et al. (Advances in Astronomy)
During the last years, a number of telescopes have been dedicated to the followup of the GRBs. But after the Swift launch, the average observed intensity of the GRBs showed to be lower than thought before. Our experience with the robotic 60 cm REM telescope confirmed this evidence, with a large number of lost GRBs. Then, we proposed to study the feasibility of a 4 m fast pointing class telescope, equipped with a multichannel imagers, from Visible to Near Infrared. In this paper, we present the main result of the feasibility study we performed so far.